Jurisprudência expressionista de direitos: uma perspectiva deleuziana - Schneider, Paulo Roberto (2021)
This paper works with the paradoxical statements of Deleuze, that is not the legislation, not even the Human Rights that create the Law, but it is the jurisprudence. Deleuze has not written anything specifically about this topic and he has only talked about it in interviews that were published in Dialogues and in the Gilles Deleuze’s Alphabet Book. The hypothesis is that the notion of jurisprudence as a creator of rights can be made under the surface expressionist scope and that its effectuation is only reached when the users are part of the rights production. Based on the hints given in the interviews by Deleuze and, henceforward, published, this thesis is organized in four chapters with the following themes and references: 1st) it presents a positivist juridical approach of the Law from the perspective of Kelsen’s Pure Theory of Law, which is, the main juridic reference in the Western; then, it shows and discuss the reception of the Deleuzian idea of the jurisprudence in the rights field; 2nd) it approaches Deleuzian noological studies and philosophers’ images made by the author – coming from different origin and levels: from the above, the depths and the surfaces – talking about jurisprudence as the expression of a philosophical thought of the right originated from a sense logic as a happening, as an effect of the surface and not as the representative; 3rd) senses are produced to the Deleuze’s compliment to the jurisprudence, based on a passage from the right to the politics with the approach he made out of the Hume’s artifices theory and out of the “new philosophy of law”, by François Ewald, that is about the passage from the liberal right to the social right. And, after that, the research presents the Deleuze’s reading about the Spinozian expressionism according to the ways of being power claiming the relation with the practical philosophy, that is called, the ethics and the politics, what allows to characterize an expressionist jurisprudence; 4th) it presents results and explores the compliment to the jurisprudence related to the necessity of the users’ participation for the rights production which opposed the Human Rights critics. To do so, it approaches the jurisprudence cases referred by the philosopher – the abortion decriminalization in France, the tobacco control and the Armenic genocide – and how a jurisprudence of surfaces can be the expression of the singular powers of the law, in so much as it considers the coexistence of macro and micro politics power lines in the inner of the society and its institutions. Considering this organization, the Thesis research refers to a surface expressionist jurisprudence as a competence of linguistic, ethics and politics order. Through the experimentation it is able to create laws in return for the life criteria, differing from a technical and jurisdictional device promoted by a set of a Justice operatives with an interpretative function of the law performed by judges.